Demand response with heat pumps: Practical implementation of three different control options - Crawley, Jenny; Martin-Vilaseca, Adria; Wingfield, Jez; Gill, Zachary; Shipworth, Michelle; Elwell, Clifford (Building services engineering research & technology, 2023)
The electrification of heating and transport and decarbonisation of supply creates a need for demand side flexibility to balance the grid. Heat pumps are expected to form a major part of heat delivery, and many modelling studies have investigated the technical potential of heat pump demand response. However, little empirical work has been reported on the practical implementation of such demand response in occupied homes. This paper presents a cross-case comparison of three early adopters of heat pump demand response in the UK. The aim was to reduce heat pump electricity consumption during the same peak period, but each employed a different control strategy: lowered air temperature setpoints, lowered flow temperature and blocked heat pump compressor. A 56–90% electricity reduction during the peak period was observed; the success of the demand response depended on how the control strategy affected the heat pump and the rest of the heating system. However, no one stakeholder is responsible for all these system components. The fabric, heating distribution and control system and heat pumps installed are highly heterogeneous across the stock, highlighting that flexibility mechanisms must be developed that can be tailored to or work across their range. Practical application Three case studies of different heat pump demand response control strategies in real homes are presented. All three households reduced their electricity consumption during a peak period but delivered unintended consequences where the heat pump’s logic did not correspond to the demand response requirements. This study highlights that the implementation of heat pump demand response to support electricity system operation requires a clear definition of electricity system need as well as practical demand response mechanisms to be integrated into heating system design.